A Case with Double Outlet Right Ventricle Caught Pre-Pregnancy Care [Gebelik Oncesi Bakimda Yakalanan Bir Cift Cikimli Sag Ventrikul Olgusu] - Sultan Oksuz; Emsal Pinar Topdagi Yilmaz; Asuman Bihter Guven Pirim; Yasemin Cayir (Medicine Science, 2014)
Double outlet right ventricle (DORV) is an uncommon congenital heart disease with symptomatic at early age. It is a ventricle-arterial connection anomaly that is defined originated from the right ventricle to the pulmonary artery and aorta by morphologically. Anomaly is accompanied usually ventricular septal defect (VSD) and pulmonary stenosis. A variety of clinical findings may present according to congenital cardiac anomalies with accompanying. Pre-pregnancy care is important at least as pregnancy care. The aim of it is to identify risk factors that are present before pregnancy, to provide information and medical support, and to provide to begin after under control of these risk factors to the pregnancy. In this article, a case who applied to take pre-conception counseling and previously unaware of presented a life threatening cardiac anomaly that is rarely seen will be presented. [Med-Science 2014; 3(4.000): 1685-90]